Integration of the Semantic Memorization Method and Tafsir Al-Ibriz at Tarbiyatussibyan Islamic Boarding School Jepara - Zakiya Faridatul Fatimah; Fathur Rohman (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This research is motivated by the high prevalence of learning fatigue and mechanical rote memorization in conventional tahfidz programs, which often focus solely on phonetic recitation without conceptual understanding. This study aims to explore the implementation of the Semantic Memorization Method and contextual reinforcement based on Tafsir Al-Ibriz in supporting students' memory retention at the Tarbiyatussibyan Islamic Boarding School, Jepara. A descriptive qualitative method was employed, with data collected through observation, documentation, and in-depth interviews involving 15 students, the boarding school leader, and the tahfidz teacher as key informants. The findings indicate that the Semantic Memorization Method successfully shifts the memorization paradigm from a mechanical process to a meaningful learning experience. The use of Tafsir Al-Ibriz served as a contextual bridge, enabling students to comprehend verses within their cultural environment, thereby facilitating a faster memory recall process. Although a challenge in dividing focus between understanding meaning and maintaining tajweed accuracy was identified, the separation of specialized tajweed sessions effectively resolved this issue. The novelty of this study lies in integrating semantic understanding with local contextual reinforcement, providing a systematic tahfidz learning model that produces robust memory retention without compromising recitation quality.